Lipid profile and nutritional quality of canned fish species in vegetable oil : matrinxã (Brycon amazonicus) and freshwater sardine (Hemiodus unicamculatus) - Freitas Pires, Caroline Roberta (2023)
Fil: Freitas Pires, Caroline Roberta. Universidade Federal do Tocantins (UFT); Brasil.